Thermal Stresses Distribution Induced in a Chimney Shell Structure of a Power Plant - J. Al-Horan, Khalid (Anbar Journal of Engineering Sciences, 2008)
In The present work, a thermal analysis of two different chimneys by studying the effect of the flue gases on the chimney shell structure was presented. A computer program was constructing using Fortran language to estimate the thermal stresses that: radial, circumferential and longitudinal thermal stresses which will induced as a result of thermal gradient across the chimney wall structure. The results show, the radial thermal stresses has the minimum value at the middle of the concrete layer in the unlined chimney. The circumferential and longitudinal thermal stresses are transferred from the negative value to the positive value. The maximum value of stresses is found in the inner surface negative value and on the outer surface positive value of the chimney.